2019
DOI: 10.1038/s41598-019-55497-w
|View full text |Cite
|
Sign up to set email alerts
|

MS-based proteomic analysis of cardiac response to hypoxia in the goldfish (Carassius auratus)

Abstract: The exceptional hypoxia tolerance of the goldfish heart may be achieved through the activation of an alternative mechanism recruiting the first product of the anaerobic glycolysis (i.e. piruvate). This hypothesis led to design a classical mass spectrometry based proteomic study to identify in the goldfish cardiac proteins that may be associated with maintaining heart function under normoxia and hypoxia. A selective protein solubilization, SDS PAGE, trypsin digestion and MALDI MS/MS analysis allowed the identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…The remarkable ability of the goldfish heart to enhance its basal performance when exposed to a hypoxic milieu has been largely documented by studies from our laboratory [7,8,12]. These studies reported that in C. auratus, exposure to hypoxia is accompanied by an increased expression of cardiac HIF-1α (hypoxia-inducible factor 1α) and NOS.…”
Section: Pi3-k/akt/nos/no Pathway Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…The remarkable ability of the goldfish heart to enhance its basal performance when exposed to a hypoxic milieu has been largely documented by studies from our laboratory [7,8,12]. These studies reported that in C. auratus, exposure to hypoxia is accompanied by an increased expression of cardiac HIF-1α (hypoxia-inducible factor 1α) and NOS.…”
Section: Pi3-k/akt/nos/no Pathway Activationmentioning
confidence: 99%
“…Thus, they represent valuable experimental models for studying the physiological strategies that allow animals to survive with reduced oxygen. In several fish species, the resistance to protracted hypoxia/anoxia is supported by a preserved cardiac activity and autonomic cardiovascular control [ 7 , 8 , 9 ]. This allows them not only to mobilize glucose from hepatic glycogen stores to all tissues, but also to transport lactate to the muscle, where it is converted into the less harmful ethanol, rapidly removed via the branchial epithelium [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of the hypoxic responses of proteomes in other organs and tissues of fish remain limited. For example, in the heart of goldfish, hypoxia deregulated five enzymes involved in glycolysis and gluconeogenesis, including fructose-1,6-bisphosphate aldolase (Imbrogno et al, 2019). Presently, we attempted to elucidate the proteomic changes of fish brains after short-term and multi-generational hypoxia exposures.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the enhancement of myocardial contractility observed in the goldfish in response to low O 2 is associated with a low accumulation of cardiac lactate. In addition, authors reported a parallel slight reduction in pyruvate levels (Imbrogno et al 2019a): this implies the activation of alternative metabolic pathways (e.g., gluconeogenesis) which, by allowing a reutilization of the first product of the anaerobic glycolysis, enhance anaerobic ATP yield and minimize metabolic acidosis. Mass spectrometry-based proteomic analysis led to the identification of two isoforms of fructose-bisphosphate aldolase differently expressed in homogenates of goldfish heart exposed to normoxic or hypoxic medium (Imbrogno et al 2019a).…”
Section: Hypoxiamentioning
confidence: 99%
“…In addition, authors reported a parallel slight reduction in pyruvate levels (Imbrogno et al 2019a): this implies the activation of alternative metabolic pathways (e.g., gluconeogenesis) which, by allowing a reutilization of the first product of the anaerobic glycolysis, enhance anaerobic ATP yield and minimize metabolic acidosis. Mass spectrometry-based proteomic analysis led to the identification of two isoforms of fructose-bisphosphate aldolase differently expressed in homogenates of goldfish heart exposed to normoxic or hypoxic medium (Imbrogno et al 2019a). Particularly, Aldolase C, mainly effective in glycolysis (Penhoet et al 1969;Penhoet and Rutter 1971), has been found in the normoxic heart, while aldolase B, which has evolved to have a role in gluconeogenesis (Penhoet and Rutter 1971;Penhoet et al 1969), has been mainly revealed in the hypoxic counterpart (Imbrogno et al 2019a).…”
Section: Hypoxiamentioning
confidence: 99%